Tipologi Nasabah dan Perspektif Emik Terhadap Bank Syariah: Sebuah Pendekatan Konstruktivisme - Nori Anggraini; Muhammad Sholihin (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The research uses the qualitative approach. It is applied the constructivism paradigm. Based on data, it can be summaries that society mada a decision to be a consumer of Islamic Bank because of the external factors. These factors, then, a main element which constructs the emic perspective, oftenly. It is foundation to conclude the consumers pattern of islamic bank. The study shows various type of consumers such as the followers-functional and excited; functional, and symphaty and functional. Keywords : Emic Perspective, Typology of islamic bank consumers, constructivism, islamic bank, and Paradigm